HUBUNGAN ANTARA KINERJA PETUGAS KESEHATAN POSYANDU DENGAN TINGKAT KEPUASAN IBU BALITA PENGGUNA POSYANDU DI PACITAN - rosita, ani (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2017)
ABSTRACT One of public health center’s program that needed public participation was Posyandu. It Consits of five tables, the fist table for registration, second table for child weighing ,third table for KMS, forth table for health education, and the last for imunication. In fact realitation of this program for the first, second and third table had done well. But the others did not exactly. And They disappointed about the service. This research aimed to analyze corelation between Posyandu provider performance with satisfaction level of child mother in Sempu Village Posyandu at the job area of Nawangan public health center, Pacitan. Design of this research was cross sectional study, the population are all of Sempu Posyandu members, it has done in Januari 25 to 28 Januari 2010. Samples are 192 Posyandu members who included in criteria. The data collected with observation and kuesioner, then analyzed with spearman rank test,and significan level at < 0,005. The result showed there was corelation between provider performance with satisfaction level of posyandu member with signifikan level p: 0,000 and coeficien correlation r : 0,988. It can be concluded, there are Correlation between posyandu provider performance with satisfaction level of child mother in Sempu Village posyandu at the job area of Nawangan public health center Pacitan. Good provider performance will increase satisfaction level of child mother. So recomended to increase provider performance in Sempu Posyandu. Keywords: Posyandu, Provider, Performance, Receiver, Satisfaction